Analysis of plant oil-based fuel characteristics for green supply chains - Sua, Lutfu S.; Balo, Figen (Elsevier, 2021)
Automotive industry has been using diesel and gasoline for a long time. But along with the variable oil prices, declining oil supplies drive people to obtain alternative fuel sources. Sustainable fuel options could change the consumption of electricity, resulting in less emission levels, less carbon, and a greater fuel supply. In general, it is a difficult task for decision-makers to find the best feasible fuel among multiple choices for the logistics industry due to the complex task of considering different performance attributes and the lack of available knowledge. As the companies strive toward cutting their supply chain costs further down and responding to the increasing pressure of “greening” their supply chains, search for more sustainable energy sources continues to draw attention. The right choice of the most feasible fuel alternative for the automotive industry will, however, effectively alleviate severe environmental problems and energy overconsumption during transportation. This study compares various types of available options for plant oil-based fuel, such as castor, coconut, corn, cotton-seed, etc., in relation to the critical characteristics described within the scope of this study. The quantitative evaluation model used in this study provides decision-makers with a tool to be used during significant strategic decision-making phases on fuel policy issues. The applied model offers quantitative conclusions that can help improve decision-making success. © 2021 Elsevier Inc. All rights reserved.
Keywords: Alternative fuel; Biofuel; Green supply chain; Plant oil; Renewable energy